The zygomatic implant perforated (ZIP) flap: a new technique for combined surgical reconstruction and rapid fixed dental rehabilitation following low-level maxillectomy - C. J. Butterworth; S. N. Rogers (International Journal of Implant Dentistry, 2017)
Abstract This aim of this report is to describe the development and evolution of a new surgical technique for the immediate surgical reconstruction and rapid post-operative prosthodontic rehabilitation with a fixed dental prosthesis following low-level maxillectomy for malignant disease. The technique involves the use of a zygomatic oncology implant perforated micro-vascular soft tissue flap (ZIP flap) for the primary management of maxillary malignancy with surgical closure of the resultant maxillary defect and the installation of osseointegrated support for a zygomatic implant-supported maxillary fixed dental prosthesis. The use of this technique facilitates extremely rapid oral and dental rehabilitation within a few weeks of resective surgery, providing rapid return to function and restoring appearance following low-level maxillary resection, even in cases where radiotherapy is required as an adjuvant treatment post-operatively. The ZIP flap technique has been adopted as a standard procedure in the unit for the management of low-level maxillary malignancy, and this report provides a detailed step-by-step approach to treatment and discusses modifications developed over the treatment of an initial cohort of patients.